(untitled) (Prosiding Konseling Kearifan Nusantara (KKN), 2025)
Career planning is important for students, especially high school students to preparing for a future that suits their interests and potential. However, students often face various obstacles, such as confusion and a lack of understanding of their interests and potential. Self-efficacy has a role in students’ career planning in facing these obstacles. Self-efficacy is belief in one’s abilities. The existence of self-efficacy can help students overcome obstacles in career planning, increase motivation, encourage courage in facing challenges, and make career decisions rationally and realistically. This article aims to review the importance of self-efficacy in student career planning. By strengthening self-efficacy through training and experience, students are expected to be able to plan their careers more maturely, be able to face challenges with confidence and make career decisions that suit their interests and potential.